Implementing project based learning to engage 6th grader students in the English class at a public institution in Medellin. (2017)
ABSTRACT: This action research project was designed to understand how the implementation of project based learning impacts the engagement of 6 graders students in the English class. This project was carried out at Francisco Miranda public Institution during two school terms with a group of six grade. The data was collected through a semi-structured interview to the cooperative teacher, a final presentation of the students and personal journals that were triangulated for the analysis. Findings revealed that project based learning promote not only engagement that empowered the students in their learning process but also group work, nonetheless it not mean that student’s misbehavior is going to decrease in the classroom.